Attitudinal and behavioral consequences of work-family conflict and family-work conflict - Does gender matter? - Yavas, Ugur; Babakus, Emin; Karatepe, Osman M. (Emerald Group Publishing Ltd, 2008)
Purpose - The purpose of this paper is to develop and test a conceptual model to examine the effects of work-family conflict, family-work conflict, and emotional exhaustion on job performance and turnover intentions. The paper also aims to investigate the role of gender as a moderator of the posited relationships. Design/methodology/approach - A sample of frontline hotel employees in Turkey serves as the study setting. Data were collected via self-administered questionnaires. A total of 723 usable responses were obtained. Findings - The results show that employees facing conflicts originating from their work (family) and family (work) roles become emotionally exhausted. These two forms of interrole conflicts are also significant predictors of frontline employees' turnover intentions. Gender moderates several of the relationships proposed in this paper. Practical implications - Turkish hotels will benefit from establishing a family-supportive work environment to lessen the detrimental impact of conflicts in the work-family interface on frontline employees' emotional exhaustion and job outcomes. A dual (i.e. gender-specific) approach appears to hold promise in managing frontline employees. Originality/value - When these results are compared to the results of studies conducted in western countries, a number of similarities become evident. These similarities broadly suggest that research findings derived from western countries are generalizable into a culturally different setting, and support the premise that as traditional gender roles continue to expand and change, a convergence of findings in work-family research takes place cross-culturally.
Keywords: family; role conflicts; employee attitudes; gender; hotels; Turkey